The radiological and electrophysiological characteristics of Hirayama disease with proximal involvement: A retrospective study - Wang, Hongwei; Tian, Ye; Wu, Jianwei; Sun, Chi; Nie, Cong; Zheng, Chaojun; Zou, Fei; Xia, Xinlei; Ma, Xiaosheng; Lyu, Feizhou; Jiang, Jianyuan; Wang, Hongli (Frontiers in Neurology, 2022)
Purpose Hirayama disease (HD) has been largely believed to affect only distal muscles. However, the proximal upper extremities have been affected in some cases, which can be confused with motor neuron diseases. Methods Baseline data, deep tendon reflex, Hoffmann sign, cervical curvature, sagittal Cobb angle, atrophied spinal cord, high signal intensity, loss of attachment, and affected muscles and segments on electromyography (EMG) were retrospectively obtained and compared between patients with HD with proximal involvement and patients with simple distal HD in one center from September 2007 to April 2022. Results In this study, fifteen patients with proximal HD and 30 patients with simple distal HD were included. The proximal group had a larger proportion of patients with decreased biceps reflex, decreased triceps reflex, brisk or hyperactive knee reflex, positive Hoffmann sign, and cervical kyphosis. The curvatures of the upper part of the cervical spine (C2-4) were lost to a greater degree in the proximal group. More affected segments were observed on magnetic resonance imaging (MRI) and electromyography in the proximal group. Conclusion The injured segments were longer and the upper curvature of the cervical spine was poorer in patients with HD with proximal involvement. These findings indicated that proximal involvement may indicate more serious HD.